Apontamentos sobre as práticas psicológicas desenvolvidas nas entidades assistenciais que atendem a crianças e adolescentes pobres - Benelli, Sílvio José [UNESP] (My University, 2013)
Notes on the psychological practices developed in social work entities that serve poor children and adolescents We understand that psychology, along with Pedagogy is part of the assumptions that compose the multidisciplinary field that comprises the socioeducative action of social work entities that serve poor children and adolescents considered in “personal and social risk”. What kinds of Psychology practices could be found in these institutions? We find evidence that the age minority logic still in force in many social work entities - that implement predominantly disciplinary and repressive, correctional and shaping forms of care, - dispense with psychology as a social transformation practice. When we find professional psychologists in social work entities, it is not uncommon for them to develop extremely traditional, psychotherapeutic, patologization actions for the individual, and to promote actions of orthopedic behavior, and therefore they may be called "technicians of conduct." This psychology is not aligned with the citizen and empowering perspective proposed by the Statute of Children and Adolescent, based on the fundamental concept of the social subject of rights.

Entendemos que a Psicologia, juntamente com a Pedagogia, faz parte dos pressupostos que compõem o campo multidisciplinar que compreende a ação socioeducativa das entidades assistenciais que atendem a crianças e a adolescentes pobres, considerados em “situação pessoal e social de risco”. Que tipos de práticas psicológicas poderiam ser encontradas nesses estabelecimentos? Encontramos evidências de que a lógica menorista ainda em vigor em muitas entidades assistenciais – que implementam formas assistenciais predominantemente disciplinares e repressivas, correcionais e modeladoras – prescinde da Psicologia como prática social transformadora. Quando encontramos profissionais psicólogos nas entidades assistenciais, não é incomum que eles desenvolvam ações extremamente tradicionais, psicoterapêuticas, patologizantes do indivíduo e promotoras de ortopedia do comportamento, podendo ser denominados de “técnicos da conduta”. Essa psicologia não está alinhada com a perspectiva cidadã e emancipadora proposta pelo Estatuto da Criança e do Adolescente, pautada na noção fundamental de sujeito social de direitos.
Keywords: Psychology practices; Social work; Social work entities; Children and adolescents; State policies; Práticas psicológicas; Assistência social; Entidades assistenciais; Crianças e adolescentes; Políticas de Estado